Early endoscopic realignment of traumatic anterior and posterior urethral disruptions under caudal anaesthesia- a 5-year review (2010)
Objective: We recently described early rigid retrograde endoscopic realignment of the disrupted urethra under caudal anaesthesia in the outpatient setting. This retrospective study was performed to evaluate our medium-term results. Patints and methods: A retrospective review of patients who had early rigid retrograde endoscopic realignment of traumatic urethral disruptions in our institution over a 5 -year period was done and relevant data extracted was analyzed. Results: Fourteen acutely ruptured urethras (10 psoterior and four anterior) were endoscopically realigned early in the study period. Nine (90%) of the posterior disruptions occured at bulbo-membranous urethra (distal to the external sphincter mechanism). Thirteen of the rupted urethras (93%) were successfully realigned (nine posterior and four anterior) and postoperative clean intermitten self-callibration (CIC) was instituted in 10 patients. The mean follow-up period was 36.6 months (range 18-54 months). The meanoperating time and the median hospital stay were 22min(range8-68min) and 3 days (range 1-10 days), respectively, and were shorter in patients with injuries of the anterior urethra than those with potent and continent. Two patients required additional procedures (direct vision internal urethrotomy or urethral dilation) and one patient has remianed on CIC. i.e. a stricture rate of 21%. Conclusion: Early retrograde endoscopic realignment under caudal analgesia is sutiable and cost-effective for patients with acute traumatic urethral disruptions and has good meduim-term results. In additon, an early psot-operative regimen of CIC significantly reduced stricture-formation in our series.